Load response of a 15 MW floating offshore wind turbine under wind-wave conditions using a fully coupled free-wake vortex model - Zedong Wang; Chusen Lin; Songtao Wang; Yuming Yuan; Hengming Zhang; Binzhen Zhou; Zhiqiang Hu; Yan Chen (Ocean Engineering, 2026)

Hydrodynamic Performance Assessment of a Hybrid Wave Energy Converter Array–Floating Breakwater System Under Irregular Waves - Hengming Zhang; Chusen Lin; Chengrong Wang; Xu Huang; Yifeng Yang; Binzhen Zhou; Yingyi Liu; Yuming Yuan (Journal of Marine Science and Engineering, 2026)
A hybrid system combining wave energy converters (WECs) and a floating breakwater presents significant potential for developing commercial-scale wave power operations. The assessment of the hydrodynamic characteristics of a WEC array–floating breakwater system under irregular waves remains in the early stages and requires further investigation. Based on the linear potential theory, a time-domain numerical model is established to evaluate the performance of a hybrid WEC array–floating breakwater system in a target sea area. The interaction between the WECs and the floating breakwater is analyzed. Results show that for the hybrid system with a triangular-baffle-type WEC array under irregular waves, the annual average wave power is 1.16 MW and the annual energy production is 10.16 × 103 MW·h, representing a 241.2% improvement compared with that of the isolated WEC array. The standard deviations of the mooring forces for the hybrid system with the triangular-baffle-type WEC array are reduced by 13.8% in the surge direction and 26.9% in the pitch direction, while increasing by 90.0% in the heave direction. Similar conclusions are obtained for the motion of the floating breakwater. The findings and data reported in this study provide guidance for the engineering application of a hybrid WEC array–floating breakwater system.

Enhancing thermospheric density modeling using bias factor analysis - Yao Wu; Junyu Chen; Chusen Lin; Zijie Li; Yaobin Fang; Yu Wu (Advances in Space Research, 2026)

Novel design and performance evaluation of a hybrid system of floating offshore wind turbine and Sharp-Eagle WECs - Chusen Lin; Qi Zhang; Songwei Sheng; Binzhen Zhou; Rouxuan Xiang; Xiushan Wu; Zhaoming Zhou; Peng Jin (Ocean Engineering, 2025)

Hydrodynamic performance and narrow gap resonance of WEC-floating breakwater hybrid system: An experimental study - Binzhen Zhou; Chusen Lin; Xu Huang; Qi Zhang; Yuan Yuming; Hengming Zhang; Peng Jin; Yifeng Yang (Ocean Engineering, 2025)

Optimization of low-earth orbit density model based on support vector regression - Yao Wu; Junyu Chen; Chusen Lin; Zijie Li (Advances in Space Research, 2025)

A method for compensating prediction errors to improve the orbit prediction accuracy of Starlink satellites - Chusen Lin; Junyu Chen; Haoze Zhu (GPS Solutions, 2025)

Annual performance and dynamic characteristics of a hybrid wind-wave floating energy system at a localized site in the North Sea - Binzhen Zhou; Zhi Zheng; Jianjian Hu; Chusen Lin; Peng Jin; Lei Wang; Yingyi Liu (Ocean Engineering, 2023)